2010
DOI: 10.1007/s10266-010-0131-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of cervical lymph node metastasis to histopathological malignancy grade, tumor angiogenesis, and lymphatic invasion in tongue cancer

Abstract: Cervical lymph node (CLN) metastasis from oral cancer correlates with poor prognosis. Therefore, accurate assessment of CLN status is crucial in treatment planning. However, there are few reports focusing on CLN metastasis from tongue cancer. Further, the growth and progress of the tumor are known to be profoundly related to histological malignancy, tumor angiogenesis, and lymphangiogenesis. Thus, this study aimed to identify predictive factors for CLN metastasis in tongue squamous cell carcinoma (SCC). Initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
1
19
0
1
Order By: Relevance
“…It can show an increased vascularity within the tumor (blood flow), microvascular changes, size of the lesion and its thickness and the distance between mucous membrane and the front of the tumor [44]. The formation of new vessels can have a prognostic value [45,46]. Intrapapillary capillary loops of the mucous membrane have been recently studied with narrow-band imaging.…”
Section: Imaging Methods In Oral Cancermentioning
confidence: 99%
“…It can show an increased vascularity within the tumor (blood flow), microvascular changes, size of the lesion and its thickness and the distance between mucous membrane and the front of the tumor [44]. The formation of new vessels can have a prognostic value [45,46]. Intrapapillary capillary loops of the mucous membrane have been recently studied with narrow-band imaging.…”
Section: Imaging Methods In Oral Cancermentioning
confidence: 99%
“…In cancers of the oral cavity, high histopathological malignancy grade is associated with increased risks of metastases to cervical lymph nodes, lung and bone, which greatly impact the prognosis [1][2][3][4][5][6] . Moreover, early detection of these cancers is desirable so that treatment can aim at conservation of oral functions and improvement of prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…13 A high vascular density is reportedly associated with advanced tumour stage and a poor prognosis in oral cancers. [11][12][13] We therefore postulated that quantitative evaluation of the vascularity of tongue cancers on Doppler intraoral ultrasonography images predict the grade of malignancy and occurrence of cervical lymph node metastasis and accordingly devise three quantitative indexes of vascularity, the BAR, BNR and BWR. The BAR, which is a measure of the quantity of blood flow within a cancer, did not differ significantly between patients with and without cervical lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%
“…10 High blood vessel density and histological grade of malignancy are significantly related to cervical lymph node metastasis in patients with oral squamouscell carcinoma. [11][12][13] Shinozaki et al 5 reported that the presence of blood vessel infiltration is a determinant of prognosis of cervical lymph node metastasis and that Doppler-identified blood vessel infiltration and lymph duct infiltration have significantly different associations with prognosis. However, no studies have used Doppler intraoral ultrasonography images to quantitatively evaluate vascularity within tumours and in their invasion fronts.…”
Section: Introductionmentioning
confidence: 99%